On-admission serum soluble CD40 ligand level predicts subsequent myocardial damage in acute myocardial infarction - Budi Yuli Setianto Anggoro Budi Hartopo Putrika Prastuti Ratna Gharini (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: Platelet activation plays an important role in plaque rupture and thrombus formation. Activated platelets release soluble CD40 ligand (sCD40LI. It has coagulation and inflammation properties. Enhanced sCD40L activity has been found in acute myocardial infarction, especially in ST-elevation myocardial infarction. The impact of this enhancement on the degree of myocardial damage remains uncertain, although evidence suggests association between sCD40L level and high burden coronary thrombus.Objective: The aim of this study was to find out whether serum sCD40L level on-admission is predictive of subsequent myocardial damage following acute myocardial infarction.Methods: This study was a cross-sectional study. We consecutively enrolled patients with acute myocardial infarction admitted to ICCU Dr. Sardjito Hospital with onset < 24 hours. Blood collection for analysis of sCD40L was withdrawn on-admission before revascularization and heparinization. Serial measurement of creatine kinase (CK-MBllevel in first 24 hours of admission was conducted, the highest level was considered a peak level that reflected myocardial damage. Troponin I was measured in single sample during 72 hours of admission. The association between serum sCD40L and peak CK-MB level was analyzed with Pearson correlation test. Statistical significancy was determined by p value < 0.05.Result: We enrolled 54 consecutive subjects, among them 37 subjects was STEM!. There was a significantly positive correlation between on-admission sCD40L and peak CK-MB level (r = 0.320 ; p value = 0.0201. Nonetheless, sCD40L did not correlate with troponin I level. In STEM I, this correlation was stronger (r = 0.424; p value = 0.0101 and even more stronger in patients with STEMI who underwent revascularization therapy (r = 0.515 ; p value = 0.0291.Conclusion: On-admission serum sCD40L level is predictive of subsequent myocardial damage following acute myocardial infarctionKey words: soluble CD40 ligand - platelet activation - acute myocardial infarction - peak CK-MB myocardial damage